2017
DOI: 10.1007/s11356-017-9104-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cadmium on cytosine hydroxymethylation in gastropod hepatopancreas

Abstract: 5-Hydroxymethylcytosine (5hmC) is an important, yet poorly understood epigenetic DNA modification, especially in invertebrates. Aberrant genome-wide 5hmC levels have been associated with cadmium (Cd) exposure in humans, but such information is lacking for invertebrate bioindicators. Here, we aimed to determine whether this epigenetic mark is present in DNA of the hepatopancreas of the land snail Cantareus aspersus and is responsive to Cd exposure. Adult snails were reared under laboratory conditions and expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 60 publications
5
13
0
Order By: Relevance
“…Thus our ICP‐MS results corroborate studies reported earlier (Rocha et al ; Rocha et al ; Nica et al ). Moreover, these findings also led us to suppose that cadmium exposure alone does not reflect the overall toxicity of suspensions of quantum dots to adult B. glabrata mollusks.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus our ICP‐MS results corroborate studies reported earlier (Rocha et al ; Rocha et al ; Nica et al ). Moreover, these findings also led us to suppose that cadmium exposure alone does not reflect the overall toxicity of suspensions of quantum dots to adult B. glabrata mollusks.…”
Section: Discussionsupporting
confidence: 93%
“…also found a lower accumulation when M. galloprovincialis were exposed to quantum dots or cadmium ions, with a relative percentage of approximately 3.4 and 14%, respectively. Thus our ICP-MS results corroborate studies reported earlier (Rocha et al 2014;Rocha et al 2015a;Nica et al 2017). Moreover, these findings also led us to suppose that cadmium exposure alone does not reflect the overall toxicity of suspensions of quantum dots to adult B. glabrata mollusks.…”
Section: Discussionsupporting
confidence: 91%
“…Cadmium (Cd) is a non-essential trace metal classified as a global priority pollutant due to its environmental persistence, bio-accumulative nature, and high toxicity at low ambient concentrations [1][2][3]. Decades of toxicological research have yielded a compelling body of evidence for the cellular, physiological, and genetic implications of exposure to Cd and its compounds [2,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have examined the retention of dietary cadmium in the soft tissues of land snails (Russell et al, 1981;Berger and Dallinger, 1989;Laskowski and Hopkin, 1996;Gomot, 1997;Notten et al, 2006;Gimbert et al, 2008;, but not at very low, but environmentally-relevant dietary levels below 0.1mg/kg dw (Nica et al, 2017b). In the current study, a 28-day exposure to doses as low as 0.2 mg/kg dw Cd (as cadmium sulfate) yielded significantly elevated hepatopancreas cadmium levels.…”
Section: Discussionmentioning
confidence: 99%
“…Cadmium sulfate will extend our knowledge on the bioavailability of different chemical forms of Cd in land snails, which is currently limited to cadmium chloride (Coeurdassier et al, 2002;Nica et al, 2015;Nica et al, 2017aNica et al, , 2017b and cadmium nitrate (Laskowski and Hopkin, 1996).…”
Section: Breeding Methodsmentioning
confidence: 99%